Effects of Set Configuration of Resistance Exercise on Perceived Exertion. Issue 3 (December 2014) - Mayo, Xián; Iglesias-Soler, Eliseo; Fernández-Del-Olmo, Miguel
Set configuration refers to the repetitions performed with regard to the maximum possible number of repetitions, a factor affecting RPE that has not been previously studied. This study analyzed the effect of set configuration and muscle mass on RPE. Eight students ( M age = 23.7 yr. ± 1.7) completed four sessions corresponding to types of exercise with different amount of muscle mass (bench press and parallel squat) and two set configurations: a session with five sets of repetitions to failure and a cluster session. The cluster session involved the same intensity, volume, and rest than the failure session, guaranteeing the same work-to-rest ratio. RPE was higher in Failure vs Cluster sessions and higher in parallel squat vs bench press. This suggests that set configuration influences RPE. Similarly, RPE can be affected by the muscle mass of the exercise performed.